Skill Development of Secondary Students for Application of Drones: Are We Ready (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
A drone refers to an unmanned aerial vehicle or a remotely piloted aircraft. Integrating drone technology into vocational education for school students can offer an exciting opportunity to them besides equipping them with valuable skills relevant to today’s rapidly evolving job market. Drones have numerous applications across various industries or sectors, making them an ideal subject for vocational education. This paper explores the various aspects of integrating drone technology in education and the challenges and concerns of teaching drones to secondary students, by seeking opinion of the variety of stakeholders. The study gathered responses through an online survey regarding familiarity of the stakeholders about drones, level of interest in learning about drones and their applications, preferred subject areas for integration, specific applications of drones, perceived benefits of skill development, opinion on teaching students about coding for drones, potential enhancement of learning experiences, anticipated concerns, and challenges, availability of teaching-learning materials, and interest in receiving skill training. The survey on the skill development of secondary students for the application of drones has provided valuable insights into the readiness and perspectives regarding the integration of drones into secondary education. The findings reveal that a majority of the respondents were aware about drones. The results contribute to the ongoing discourse on preparing students for the evolving technological landscape, inform future initiatives in drone education and prepare them for the future skills needed for industry 4.0. By analyzing the collected opinions, this paper provides a comprehensive understanding of the potential benefits of teaching drones, such as enhanced STEM learning, critical thinking, and problem-solving skills, as well as the challenges faced in terms of safety and privacy concerns and availability of teaching-learning materials. The paper also suggests the various aspects of drone technology, which can be integrated with subjects like Science, Maths, Social Science and Engineering or Technology.